Briar Rose - Yolen, Jane. (New York : Starscape, 2002)
In this retelling of "Sleeping Beauty," a young woman learns that her grandmother had a secret past tied to the Holocaust.
"A Tom Doherty Associates book."
Notable/Best Books (A.L.A.)
Wilson's Junior High School
Wilson's Senior High School
Book Report, December 2006
Booklist, August 1997
Keywords: Holocaust, Jewish (1939-1945) -- Fiction; Sleeping Beauty (Tale) -- Adaptations; Fairy tales; Holocaust, 1939-1945 -- Fiction; Sleeping Beauty (Tale) -- Adaptations; Fantastic fiction